Development, modernism and modernity in Africa - Agwuele, Augustine (Routledge African studies, 2012)
Introduction / Augustine Agwuele -- Part 1. Modernism-modernity: socio-cultural transformation: Between delayed modernity and deferred democracy: Africa's troubled take-off / Ali A. Mazrui -- A critique of Cornel West's "Race and modernity" / Hetty ter Haar -- Chieftaincy, collective interests and the Dagomba new elite / Deborah Pellow -- Murid identity and Wolof Ajami literature in Senegal / Fallou Ngom -- From village-square to internet-square: language and culture at the Usa-Africa dialogue series / Augustine Agwuele -- Elaloro: a didactic approach to Yoruba education / Michael O. Afoláyan -- Part 2. Modernism-modernity: arts, media and religion: The old chestnut of African cultural production: insiders and outsiders / Kenneth W. Harrow -- Strategic collaborations between Nigerians and Germans: the making of a Yorùbá culture movement / Debra Klein -- Interrogating the Africana artist: interviews, penetration, and Muholic occupation / Moyosore Okediji -- Re-imagining West African women's sexuality: Bekolo's Les saignantes and the Mevoungou / Naminata Diabate -- Matangazo ya biashara na jinsia: gender stereotypes and advertisements in Kenya / Maurice Nyamanga Amutabi -- From Kamiirithu to xyz: between cultural "flaws" and democratic change in independent Kenya / Hannington Ochwada -- African Christianity: its scope in global context / Caleb Oladipo -- Women and Islam in urban Burkina Faso: piety between definitions and interpretation / Liza Debevec -- Part 3. Development: economic and political transformation: Globalization and the governance of foreign direct investment in Africa / Roshen Hendrickson -- The Fulani land/settlement question in British Southern Cameroon, 1916-1960 / Emmanuel M. Mbah -- Imminent colonialism: violence on Lutheran mission stations and the ending of the pre-colonial Zulu State / Kirsten Rüther -- Colonialism and cultural change in Africa / Julius O. Adekunle -- Reengineering social institutions for peace and development: the case of post-genocide Rwanda / Wanjala S. Nasong'o